2020
DOI: 10.2147/rmhp.s221008
|View full text |Cite
|
Sign up to set email alerts
|

<p>Costs Analysis of Fibrin Sealant for Prevention of Anastomotic Leakage in Lower Colorectal Surgery</p>

Abstract: Introduction: Postoperative anastomotic leaks remain a common and serious complication of colorectal surgeries and are a major cause of mortality and morbidity of these procedures. Anastomotic leaks (AL) have been extensively studied; however, there has been no significant reduction in their prevalence over time. In addition, there is a significant economic burden from AL attributed to the need for repeat surgery, radiologic intervention and lengthened hospital stay. We conducted a comparative cost analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…27 Application of fibrin sealant to sutured anastomosis in lower colorectal surgery has resulted in a decrease in anastomotic leakage and a reduction in overall cost. 28 Contraindication for the use of TISSEEL is hypersensitivity to its components, particularly apotrinin, which has been reported as an allergen. Despite rigorous screening methods for pooled plasma used in the synthesis of these agents, infections have been reported with the use of fibrin sealants.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…27 Application of fibrin sealant to sutured anastomosis in lower colorectal surgery has resulted in a decrease in anastomotic leakage and a reduction in overall cost. 28 Contraindication for the use of TISSEEL is hypersensitivity to its components, particularly apotrinin, which has been reported as an allergen. Despite rigorous screening methods for pooled plasma used in the synthesis of these agents, infections have been reported with the use of fibrin sealants.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…The authors concluded that the application of fibrin sealants was not only associated with decreased AL rates but also contributed to cost savings of roughly 22% (using a potential model). These cost savings originate mainly from the reduction in the length of hospitalization due to postoperative reoperations, radiological interventions, and/or transfusions ( 67 ). These findings correlate with the observed outcomes of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin glue (FG) is a commonly used hemostatic agent in treatment of burns, cardiac diseases, and pediatric, liver, orthopedic, vascular [ 23 ], and colorectal surgeries [ 24 , 25 ]. It is produced through fibrinogen hydrolysis by the proteolytic enzyme thrombin.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be a good carrier of antibiotics, genes, growth factors, and cytostatics [ 26 ]. The use of a fibrin sealant in surgical procedures, including surgical anastomosis, reduces the costs and treatment time associated with postoperative complications, including reoperation in the case of anastomotic leakage [ 24 ]. A combination of FG and oxaliplatin (OXP) enhanced the antitumor performance of OXP in a subcutaneous and abdominal metastasis model of murine colorectal cancer [ 26 ].…”
Section: Introductionmentioning
confidence: 99%